School Bell ? an Attribute of Pupils? Daily Life - Martyniuk, Wiesława (INSTED: Interdisciplinary Studies in Education & Society, 2012)
The main intention of the conducted project was an attempt to bring closer a fragment of school daily life which covers the time of break between lessons and to recognise the meanings which are attributed by pupils to the school bell sound. The text presents results of my research, which illustrate the world of children?s meanings associated with the sound of the school bell ? an inherent attribute of pupils? daily life. What significance do they ascribe to the sound of the school bell? What does its sound really mean to them when it signals a beginning of another lesson and what when it starts a break? Such formulated questions specified the area of my empiric quests. These attempts of mine belong to the trend of research which on the one hand contributes to the fuller comprehension of childhood shown from the perspective of the very children, whereas on the other hand it may reveal senses and meanings which are given by children to the world that surrounds them.